Eficacia del manejo farmacológico de la dislipidemia en la prevención primaria de eventos cardiovasculares. - Ortiz Farez, Gerson Klington (Machala : Universidad Técnica de Machala, 2019)
Introduction: Cardiovascular disease is the main cause of morbidity and mortality a world level, it is among the leading causes of mortality in the world, closely linked to diabetes. The pharmacological control of lipids plays an important role in preventing cardiovascular events, so it is essential to recognize the patients that have the greatest benefit with this therapy. Objective: To evaluate the efficacy of lipid-lowering drugs in the primary prevention of cardiovascular events through the review of updated literature. Methodology: We searched the literature published between 2014 and 2018 in the databases Pubmed, Intramed, Medscape, Cochrane library, Elsevier, Circulation, Journal of the American College of Cardiology, American association of clinical endocrinologists, American diabetes association, European society of cardiology on the treatment of dyslipidemia. Primary prevention articles were included, as well as relevant clinical practice guidelines. The main lipid-lowering drugs were evaluated separately for an individual analysis. Conclusions: Dyslipidemia increases the risk of premature heart disease and residual risk. Statins, ezetimibe, PCSK9 inhibitors significantly reduce the risk of cardiovascular disease and mortality; they are safe in patients ≥ 75 years with diabetes and moderate CRI. The fibrates. Omega-3 supplements, drugs for low HDL-C do not demonstrate cardiovascular benefit. However, omega-3 can have benefits in high doses in selected patients.
Introducción: La enfermedad cardiovascular es la principal causa de morbimortalidad a nivel mundial, se encuentra entre las tres primeras causas de mortalidad en el mundo, muy ligada a la diabetes. El control farmacológico de los lípidos juega un rol importante para prevenir eventos cardiovasculares, por lo que es fundamental reconocer los pacientes que mayor beneficio tienen con esta terapia. Objetivo: Evaluar la eficacia de los fármacos hipolipemiantes en la prevención primaria de eventos cardiovasculares mediante la revisión de literatura actualizada. Metodología: Se realizaron búsquedas de la literatura publicada entre 2014 y 2018 en las bases de datos Pubmed, Intramed, Medscape, Cochrane library, Elsevier, Circulation, Journal of de American College of Cardiology, American association of clinical endocrinologists, American diabetes association, European society of cardiology sobre el tratamiento de la dislipidemia. Se incluyeron artículos de prevención primaria, además guías de práctica clínica relevantes. Se evaluaron los principales fármacos hipolipemiantes por separado para un análisis individual. Conclusiones: La dislipidemia aumenta el riesgo de enfermedad cardiaca prematura y el riesgo residual. Las estatinas, ezetimibe, inhibidores PCSK9 reducen significativamente el riesgo de enfermedad cardiovascular y la mortalidad; son seguros en pacientes ≥ 75 años con diabetes e IRC moderada. Los fibratos. Suplementos omega-3, fármacos para c-HDL bajo no demuestran beneficio cardiovascular. Sin embargo, omega-3 puede tener beneficios en dosis altas en pacientes seleccionados.
Keywords: HIPOLIPEMIANTES; DISLIPIDEMIAS; HDL-COLESTEROL; LDL-COLESTEROL